2015
DOI: 10.1186/s40538-015-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of early leaf removal and cluster thinning treatments on berry growth and grape composition in cultivars Vranac and Cabernet Sauvignon

Abstract: Background: The aim of the present work was to investigate the effect of early leaf removal and cluster thinning treatments in the Mediterranean climate on berry growth and how these two techniques affect phenolic profile (especially proathocyanidins) and color characteristics for later wine production. The study was conducted in 2011 in Podgorica, Montenegro. Two grapevine cultivars were selected to compare different ability in flavonoid accumulation: Vranac, with moderate accumulation and Cabernet Sauvignon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 17 publications
3
18
0
2
Order By: Relevance
“…However, it had a remarkable effect on the cluster weight, but such increase did not completely compensate the decrement in the yield weight. Our results concerning the effect of cluster thinning on yield weight and cluster weight have been confirmed by many workers (Looney and Wood, 1977;Looney, 1981;Kaps and Cahoon, 1989;Ferree et al, 2003;Dami, 2005;Reynolds et al, 2007;Gil-Muñoz et al, 2009;El-salhy et al, 2009;Kamiloglu, 2011;Zhuang et al, 2014 andBogicevic et al, 2015), they found that cluster thinning of grape cultivars reduced yield. Naor et al, 2002;Sun et al, 2012 andRescic et al, 2015 noted that the reduction of yield weight resulted from cluster thinning led to a significant increase of cluster weight.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it had a remarkable effect on the cluster weight, but such increase did not completely compensate the decrement in the yield weight. Our results concerning the effect of cluster thinning on yield weight and cluster weight have been confirmed by many workers (Looney and Wood, 1977;Looney, 1981;Kaps and Cahoon, 1989;Ferree et al, 2003;Dami, 2005;Reynolds et al, 2007;Gil-Muñoz et al, 2009;El-salhy et al, 2009;Kamiloglu, 2011;Zhuang et al, 2014 andBogicevic et al, 2015), they found that cluster thinning of grape cultivars reduced yield. Naor et al, 2002;Sun et al, 2012 andRescic et al, 2015 noted that the reduction of yield weight resulted from cluster thinning led to a significant increase of cluster weight.…”
Section: Discussionsupporting
confidence: 87%
“…Cluster thinning has been used for increasing berry and cluster weight and improving the quality of various grape cultivars especially the seedless ones. It applied alone or in combination with GA 3 treatments (Zhao et al, 2006;Mohamed and Shaaban, 2008;Damota et al, 2010;El-salhy et al, 2010;Mohsen, 2015 andBogicevic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf removal consists of removing basal leaves around the clusters in the east or north side during grape development increasing the cluster exposure to solar radiation. It is well known that an early leaf removal (before flowering) increased total soluble solids, anthocyanins, and flavonols (Tarara et al, 2008;Diago et al, 2012;Gatti et al, 2012;Pastore et al, 2013;Bogicevic et al, 2015;Cook et al, 2015;Bubola et al, 2017). However, some authors reported increases in titratable acidity in Sangiovese (Gatti et al, 2012) and Teran (Bubola et al, 2017) cultivars while other authors found decreases in acidity with basal leaf removal on Tempranillo (Diago et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…O raleio de cacho aplicado em véraison promoveu a biossíntese de proantocianidinas em 'Vranac', enquanto que em 'Cabernet Sauvignon', o aumento dos teores de proantocianidinas foi associado a menor massa das bagas (Bogicevic et al, 2015). Com relação a 'Malbec', o raleio de cacho demonstrou efeito variado sobre flavan-3-ols em duas safras (Fanzone et al, 2011).…”
Section: /9unclassified